Efficacy of a diagnostic strategy for patients with chest pain and no ST-segment elevation in the emergency room - Bassan,Roberto (2000)
PURPOSE: To evaluate the efficacy of a systematic model of care for patients with chest pain and no ST segment elevation in the emergency room. METHODS: From 1003 patients submitted to an algorithm diagnostic investigation by probability of acute ischemic syndrome. We analyzed 600 ones with no elevation of ST segment, then enrolled to diagnostic routes of median (route 2) and low probability (route 3) to ischemic syndrome. RESULTS: In route 2 we found 17% acute myocardial infarction and 43% unstable angina, whereas in route 3 the rates were 2% and 7%, respectively. Patients with normal/non--specific ECG had 6% probability of AMI whereas in those with negative first CKMB it was 7%; the association of the 2 data only reduced it to 4%. In patients in route 2 the diagnosis of AMI could only be ruled out with serial CKMB measurement up to 9 hours, while in route 3 it could be done in up to 3 hours. Thus, sensitivity and negative predictive value of admission CKMB for AMI were 52% and 93%, respectively. About one-half of patients with unstable angina did not disclose objective ischemic changes on admission. CONCLUSION: The use of a systematic model of care in patients with chest pain offers the opportunity of hindering inappropriate release of patients with ACI and reduces unnecessary admissions. However some patients even with normal ECG should not be released based on a negative first CKMB. Serial measurement of CKMB up to 9 hours is necessary in patients with medium probability of AMI.